ANALISIS WELLBEING GURU BERDASARKAN SKOR RAPOR PENDIDIKAN SDN 6 BANDA ACEH 2024–2025 - Mudassir (Lembaga Riset dan Inovasi Kreyat Center, 2025)
This study analyzes the improvement of the learning environment quality at SD Negeri 6 Banda Aceh by focusing on the psychological well-being of teachers, as reflected in the 2024 and 2025 Education Report scores. The school’s score increased from 84.78 in 2024 to 87.00 in 2025, indicating a positive shift of 2.22 points. The aim of this study is to examine the factors contributing to this increase and to describe how these changes support teachers in feeling more comfortable and connected while teaching. This descriptive study uses secondary data from the Ministry of Education's Education Report and Learning Environment Survey (Sulingjar). The findings show that improvements in school leadership, a safe and inclusive school climate, and the implementation of social-emotional learning by teachers play a crucial role. These aspects enhance teacher collaboration, reduce emotional stress, and foster a reflective and supportive school culture. The study concludes that a psychologically supportive environment positively influences teaching effectiveness and the overall quality of education in primary schools.